COVID-19 in Indonesia: Challenges and Multidisciplinary Perspectives for a Safe and Productive New Normal - Anindya Pradipta Susanto; Ardi Findyartini; Akmal Taher; Damar P Susilaradeya; Iwan Ariawan; Teguh Dartanto; Bagus Takwin; Imam Budidarmawan Prasodjo; Prasandhya Astagiri Yusuf; Pratiwi Pudjilestari Sudarmono; Ari Fahrial Syam; Budi Wiweko (Acta Medica Indonesiana, 2020)
The COVID-19 pandemic has caused disruption in all aspects of life, and countries around the world have been combating this pandemic using multiple approaches. Success in one country does not guarantee a transferable approach to other countries with different contexts. This review describes the challenges of COVID-19 management in Indonesia as a populous, socially and culturally diverse, and archipelagic country. It aims to provide multidisciplinary perspectives for a safe, evidence-based, and productive new normal as well as a comprehensive and integrated actionable policy for COVID-19 control.